Knee Osteoarthritis after Reconstruction of Isolated Anterior Cruciate Ligament Injuries: A Systematic Literature Review - Riccardo, Compagnoni; Fabio, Catani; Pietro, Randelli (Joints, 2017)
Purpose The aim of this review was to analyze the current literature on osteoarthritic evolution of knees without any combined meniscal or ligament lesions undergoing anterior cruciate ligament (ACL) reconstruction.Methods A PubMed/MEDLINE research was performed using the following keywords: “Anterior Cruciate Ligament Reconstruction” [Mesh] AND “Osteoarthritis, Knee” [Mesh]. Only English language literature and articles published after 2005 were included. Studies including concomitant meniscal tears, posterior cruciate or collateral ligament injuries, previous surgery in the affected knees, infections, osteochondral defects, loose bodies, synovial plica syndrome, and posteromedial or posterolateral corner injuries were not considered in this review.Results Twelve studies were selected. These papers included 892 patients (mean age at the time of surgery was 22.3 years), with an average follow-up of 11 years. Imaging at follow-up was obtained with standard radiographs in nine studies, magnetic resonance imaging (MRI) in one study, and both X-rays and MRI in two studies. Eight studies reported osteoarthritic evolution, with different prevalence.Conclusion Only few high-quality studies focused on these specific patients have been published. When reconstructed, isolated ACL-deficient knees have a low risk of osteoarthritic evolution, but mild signs of joint degeneration are reported by the current literature.Level of Evidence Level IV, systematic review of level I to level IV studies.
Keywords: cruciate ligament; anterior; osteoarthritis; knee; surgical procedures; operative